Analisis Kebijakan Percepatan Sertifikasi dan Tunjangan Profesi Guru Madrasah Tahun 2026 dalam Perspektif Kesejahteraan Guru - Nikmatus Sholikah; Sri Minarti (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
The policy of accelerating certification and the Madrasah Professional Teacher Allowance (TPG) in 2026 is one of the government's strategic steps to improve the professionalism and welfare of madrasah teachers in Indonesia. This study aims to analyze the policy of accelerating teacher certification through the Teacher Professional Education (PPG) program and accelerating the disbursement of TPG from the perspective of teacher welfare. The study used library research with a qualitative descriptive approach. Data were obtained from national journals, government regulations, scientific articles, official news reports from the Ministry of Religious Affairs, and various relevant literature sources.The results indicate that the policy of accelerating madrasah teacher certification in 2026 demonstrates the government's commitment to improving the quality of Islamic education and human resources in madrasahs. Teacher certification not only serves as professional recognition of teacher competence but is also a primary requirement for obtaining the Teacher Professional Allowance. The accelerated disbursement of TPG through the digital systems EMIS and SIMPATIKA has had a positive impact on teacher welfare, particularly in increasing income, work motivation, and the quality of learning in madrasahs.policy implementation still faces various obstacles, such as limited PPG quotas, delays in data validation, digital administration constraints, and unequal welfare for non-certified and honorary madrasa teachers. Furthermore, there remains a gap in access between public and private madrasa teachers to the certification program.